PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGATKAN KOLABORASI SISWA SD NEGERI 12 PALU - Moh.Fauzan; Muhammad Jamhari; Isrofiah (Jurnal Genta Mulia, 2025)
The optimal learning model is one that can meet the goals of 21st century education by integrating the 4C principles of critical thinking, communication, collaboration, and creativity. The results of initial observations made by researchers on the implementation of learning at SDN 12 Palu, Palu City showed several findings. Students tend to be passive in learning activities, less responsive to questions from the teacher, and discussion activities are not effective because students are reluctant to express ideas and opinions. This research uses the Problem Based Learning (PBL) learning model, which is expected to improve the collaborative skills of students III A SDN 12 Palu. The application of the Problem Based Learning (PBL) learning model was effective in improving students' collaboration skills. The data show an increase in the percentage of the four assessment indicators, with details as follows: indicators of productivity in work increased from 72% in cycle 1 to 86% in cycle 2, indicators of mutual responsibility increased from 70% in cycle 1 to 84% in cycle 2, indicators of compromise increased from 69% in cycle 1 to 83% in cycle 2.